Non-tandem repeat polymorphisms at microsatellite loci in wine yeast species - Raymond Eder, María Laura (2020)
Yeast microsatellite loci consist of short tandem-repeated DNA sequences of variable length. The high mutational rate at these loci generates a remarkable repertoire of alleles, useful for strain differentiation and population genetic studies. In this work, we analyze the DNA sequences of thirteen alleles from each of ten microsatellite loci described for the yeast Starmerella bacillaris. Our results show that polymorphic variants of some informative alleles are dependent on SNPs and indels rather than on length variation at their originally defined tandem-repeated motifs. The analysis was extended to 55 previously described hypervariable microsatellite loci from a total of 26 sequenced genomes of yeast species that dominate the microbiota of spontaneously fermenting grape musts (i.e., Hanseniaspora uvarum, Saccharomyces cerevisae, Saccharomyces uvarum, and Torulaspora delbrueckii) or lead to wine spoilage (Brettanomyces bruxellensis and Meyerozyma guilliermondii). We found that allelic variants for some microsatellite loci of these yeast species are also dependent on SNPs and/or indels flanking their tandem-repeated motifs. For some loci, the number of units at their tandem repeats was found to be identical among the various characterized alleles, with allelic differences being dependent exclusively on flanking polymorphisms. Our results indicate that allele sizing of microsatellite loci using PCR, although valid for strain differentiation and population genetic studies, does not necessarily score the number of units at their tandem-repeated motifs. Sequence analysis of microsatellite loci alleles could provide relevant information for evolutionary and phylogeny studies of yeast species.